The Effect of ESG Practices on Financial Performance of Public Companies in Brazil - Francisco Gomes de Silva; Michelle Quiroz Villardi; Andrade Victor Cavalcante (Aurora: Journal of Emerging Business Paradigms, 2025)
This study investigates the effect of Environmental, Social, and Governance (ESG) practices on the financial performance of publicly listed companies in Brazil. Using a quantitative research design and panel data covering 112 non-financial firms listed on B3 (Brasil Bolsa Balcão) over the period 2018–2023, this study examines whether ESG engagement contributes to firm profitability and market valuation. ESG performance is measured using standardized ESG scores obtained from international rating agencies, while financial performance is proxied by return on assets (ROA), return on equity (ROE), and Tobin’s Q. The empirical analysis employs fixed-effects panel regression with robust standard errors clustered at the firm level to control for unobserved heterogeneity, heteroskedasticity, and autocorrelation. To mitigate potential endogeneity, ESG variables are lagged by one period. The results reveal that ESG practices have a positive and statistically significant effect on all measures of financial performance. Firms with higher ESG scores exhibit superior profitability and higher market valuation, indicating that sustainability-oriented strategies function as a value-creating mechanism in the Brazilian capital market. These findings support stakeholder theory, legitimacy theory, and the resource-based view, suggesting that ESG engagement enhances corporate reputation, reduces firm risk, and strengthens long-term competitive advantage. This study contributes to the literature by providing robust empirical evidence from an emerging market characterized by institutional complexity and sustainability challenges. The findings offer important implications for corporate managers, investors, and policymakers seeking to promote sustainable and financially resilient business practices in Brazil.